Citrus Disease Identification Chart - A. Levy; J. D. Burrow; M. M. Dewdney (EDIS)
This flowchart is intended to help both commercial citrus growers and home gardeners in properly identifying common citrus diseases on fruit, leaves, and stems. Proper identification will help determine the appropriate management strategy. Written by Amit Levy, Jamie D. Burrow, and Megan M. Dewdney, and published by the UF/IFAS Plant Pathology Department. https://edis.ifas.ufl.edu/pp367